Analisis Kontibusi dan Pengaruh PDRB Sektor Pertanian, Nilai Tukar Petani, Ekspor Sektor Pertanian dan Investasi Sektor Pertanian terhadap Penyerapan Tenaga Kerja Sektor Pertanian di Provinsi Jambi - Putra, Iwan Eka; Amali, Muhammad; Oktarina, Desti (Universitas Batanghari Jambi, 2025)
The purpose of this study was to analyze the influence of the provincial GRDP of the agricultural sector, farmer exchange rates, agricultural sector exports, and agricultural sector investment on the absorption of agricultural sector labor in Jambi Province. The analysis method used is quantitative descriptive using secondary data in 2010-2023. The analysis tools used are the contribution formula and multiple linear regression. The results of this study indicate that the contribution of agricultural sector labor to the number of workers in Jambi Province is with an average contribution value of 50% which is classified as very good. Partially there is a positive but insignificant influence between the agricultural sector GRDP, farmer exchange rates and agricultural sector exports on the absorption of agricultural sector labor in Jambi Province, while agricultural sector investment has a negative and significant influence on the absorption of agricultural sector labor in Jambi Province during 2010-2023